The landscape studies of Hayman Rooke (1723-1806) : antiquarianism, archaeology and natural history in the eighteenth century - Sloan, Emily (Gender and landscape history., 2019)
After his military career, Major Hayman Rooke undertook detailed studies of landscape, ancient trees, natural history, meteorology, and ancient and Roman Britain. He was linked into a broad network of friends and correspondents, including landowners such as Earl Bathurst and the duke of Portland, and their agents (among them Humphrey Repton); he was also connected to numerous learned societies. Information from these sources, coupled with his wide-ranging reading and first-hand observations, gave him a unique perspective on the landscape. This book examines Rooke's work, showing how landscapes were interpreted and understood in the eighteenth century; more broadly, it offers new insights into the antiquarian movement of the time. It is richly illustrated, making use of many of Rooke's own sketches and drawings.